MEK inhibitors for the treatment of non-small cell lung cancer - Han, Jing; Liu, Yang; Yang, Sen; Wu, Xuan; Li, Hongle; Wang, Qiming (Journal of hematology and oncology, 2021)
BRAF and KRAS are two key oncogenes in the RAS/RAF/MEK/MAPK signaling pathway. Concomitant mutations in both KRAS and BRAF genes have been identified in non-small cell lung cancer (NSCLC). They lead to the proliferation, differentiation, and apoptosis of tumor cells by activating the RAS/RAF/MEK/ERK signaling pathway. To date, agents that target RAS/RAF/MEK/ERK signaling pathway have been investigated in NSCLC patients harboring BRAF mutations. BRAF and MEK inhibitors have gained approval for the treatment of patients with NSCLC. According to the reported findings, the combination of MEK inhibitors with chemotherapy, immune checkpoint inhibitors, epidermal growth factor receptor-tyrosine kinase inhibitors or BRAF inhibitors is highly significant for improving clinical efficacy and causing delay in the occurrence of drug resistance. This review summarized the existing experimental results and presented ongoing clinical studies as well. However, further researches need to be conducted to indicate how we can combine other drugs with MEK inhibitors to significantly increase therapeutic effects on patients with lung cancer.